Metaphorical Perceptions of Secondary School Students towards Physical Education Teachers - Rafet Ünver (Journal of Educational Issues, 2024)
As it is known, one of the most important factors of an education system is the teacher. According to Turkey’s education system, students first meet a physical education teacher in secondary school. Therefore, it is an important question that remains to be clarified what students who have just started secondary school think about their physical education teachers. In this context, the aim of the research was to examine the metaphors created by the students who have just started secondary school about physical education teachers. This research is a qualitative study designed by making use of the phenomenology pattern that examines the metaphors created by secondary school students about physical education teachers. A total of 65 students, 34 male and 31 female, participated in this research voluntarily. A structured interview form prepared to evaluate secondary school students’ perceptions of physical education teachers was used. In this study, content analysis technique was used in the evaluation of metaphors. When the research findings were examined, it was seen that 6 themes were created in total. Within the scope of these themes, it was seen that there were 12 metaphors in total. While the most metaphors were created under the theme of Superhero (29), the least metaphors were produced under the theme of Element (3). When the reasons for the themes created by the participants about physical education teachers were examined, it was determined that the students emphasized that physical education teachers are strong and athletic and also have various abilities. As a result, it was found that the justifications for all metaphors formed by secondary school students about physical education teachers were positive. Therefore, it can be said that secondary school students have positive feelings about physical education teachers.